The Guinness Book of Records 1997 - Guinness Publishing (Guinness Publishing, 1996)
Features of the 43rd edition of this long-established annual reference book include a 12-page colour section on the 1996 Olympic Games, an entry on the Internet, and coverage of recent developments in architecture, computer-games records, and 1990s music
Include Color Illustration and Index
Keywords: World records -- Curiosities and wonders